Integrasi Islam dengan Budaya Lokal di Desa Hutaimbaru Kecamatan Halongonan Kabupaten Padang Lawas Utara Studi Antropologis Tentang Penerapan Falsafah Poda Na Lima - Nasution, Yusrina (Lembaga Yasin AlSys, 2023)
Poda Na Lima is the fruit of the ancestral thought of the Mandailing tribe which still exists in today's life and becomes a guide or advice in carrying out daily life. This thesis research uses qualitative methods and conducts field research which originates from the people of Hutaimbaru Village, Halongonan District, North Padang Lawas Regency and is supported by library research. With a data collection tool in the form of in-depth interviewers, namely face-to-face question and answer to Traditional Leaders, Religious Leaders, Community Leaders and one village official. Qualitative research approaches such as speech, speech, behavior that can be observed from an individual, community group or organization in a certain setting are reviewed from a comprehensive point of view. The purpose of this study is to find out the essential meanings contained in the poda nalima as well as to find out how relevant it is to Islamic teachings.